Who Owns the Land? Litigants, Justices, Colonos, and Titleholders' Struggle to Define the Origins of Private Property in Colombia (2015)
This article explores the origin of private property in the Colombian legal system. The authors use Supreme Court case law from the twentieth century to analyze in-depth how wastelands (baldíos) come to be owned. Supreme Court decisions are organized and examined with respect to issues pertaining to appropriate modes of acquisition of wastelands, either occupation and labor or state grant, and the rules of evidence to prove whether the owner of a specific plot is the state, the titleholder or the settler (colono). This article demonstrates the difficult task of establishing simple clear rules to determine the ownership over tracts of land categorized as wastelands through the examination of the ambiguities of legislation and of the contradictory Supreme Court's rule of law. It also identifies the areas of contention, contestation and contradiction in the regulation of this matter and highlights how litigants, settlers, titleholders and Supreme Court Justices are part of a constant struggle to define the particular meaning of ownership over wastelands. © 2015 by De Gruyter.